PENAMPILAN KETAHANAN ENAM VARIETAS KACANG TANAH TERHADAP PENGGEREK POLONG (ETIELLA ZINCKENELLA TRIETSCHKE) DI DATARAN TINGGI DAN DATARAN RENDAH BENGKULU - Dwinardi Apriyanto, Burhannudin Toha riyatiningsih & D. Suryati . (Universitas Lampung, 2010)
Resistance performance of six groundnut varieties to Soybean Pod Borer (Etiella zinckenella Treitschke) at high and low elevation in Bengkulu. Soybean pod borer (SPB), Etiella zinckenella Treitschke, often caused serious pod damage and reduced pod yield in several groundnut central in Bengkulu. Field trials were conducted in two locations, Air Dingin (Rejang Lebong, 900 m asl.) and Kuro Tidur (Bengkulu Utara, 200 m asl.) to evaluate resistance performance of groundnut varieties to SPB. Six varieties, Jerapah, Kacil, Bison, Pather, Singa dan Singa, were grown in Air Dingin. Five varieties ( as above but minus Sima) were grown in Kuro Tidur. Susceptible local variety was used as control. Varieties were arranged in plots in randomized complete block design (RCBD) replicated three times, in 3 m x 5 m plots and 20 cm x 30 cm planting space. Dolomite was applied at doses of 0.333 ton ha-1 in Air Dingin and 3 ton ha-1 in Kuro Tidur. Plants were fertilized with N (Urea) - P (TSP) - K (KCl) at the nationally recommended doses (70 - 125 - 70 kg ha-1). Damaged pods and larval density were observed three times at 63, 77 and 93 day after sowing (SAW). Undamaged pods was weighted at harvest. Data were analyzed with analysis of variance and LSD to separate varietal means. The results revealed that the numbers and percetages of damaged pods incresed with plant age. Four groundnut varieties (Kancil, Panther, Singa and Sima) suffered significantly less pod damage than local variety and the other two (Jerapah and Bison), and therefore they are more resistance than the last three. Regardless of varieties, pod damage was significantly higher in Kuro Tidur than that in Air Dingin. The weight of undamage pods of resistance varieties was significantly higher than that of local, but was not significantly difference from that of Bison and Jerapah, in Air Dingin. In contrast, there was no significant different undamage pod weight between all varieties in Kuro Tidur.